2013
DOI: 10.1121/1.4816413
|View full text |Cite
|
Sign up to set email alerts
|

Role and relative contribution of temporal envelope and fine structure cues in sentence recognition by normal-hearing listeners

Abstract: The present study investigated the role and relative contribution of envelope and temporal fine structure (TFS) to sentence recognition in noise. Target and masker stimuli were added at five different signal-to-noise ratios (SNRs) and filtered into 30 contiguous frequency bands. The envelope and TFS were extracted from each band by Hilbert decomposition. The final stimuli consisted of the envelope of the target/masker sound mixture at x dB SNR and the TFS of the same sound mixture at y dB SNR. A first experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Previous studies have demonstrated that E is sufficient for speech perception Apoux et al 2013), while FS is important for pitch perception and lexical tone perception (Xu and Pfingst 2003). Mandarin Chinese is a tone language with four phonologically distinctive tones that are characterized by syllable-level fundamental frequency (F0) contour patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that E is sufficient for speech perception Apoux et al 2013), while FS is important for pitch perception and lexical tone perception (Xu and Pfingst 2003). Mandarin Chinese is a tone language with four phonologically distinctive tones that are characterized by syllable-level fundamental frequency (F0) contour patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In such conditions, it has been proposed that the frequency-modulated carrier of the signal, the acoustic temporal fine structure (TFS), may provide additional information for speech intelligibility by facilitating the glimpsing of spectro-temporal moments at favorable signal-to-noise ratios (SNR), that is, by listening in the amplitude dips of the interfering masker (Lorenzi et al, 2006;Hopkins and Moore, 2009). Recent investigations have suggested that the availability of the speech TFS during these moments of favorable SNRs may be particularly important for source segregation (Apoux et al, 2013). TFS may also be important in some intelligibility metrics (Chen et al, 2013) and play an important role in the integration of speech fragments (Gilbert and Lorenzi, 2010;Gnansia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Apoux et al (2013) presented a very instructive framework for viewing the role and contribution of the TFS to speech intelligibility, particularly in marrying the findings of previous vocoder-and chimeric-based signal processing strategies. Vocoderbased methods extract the ENV through rectification and low-pass filtering and then modulate an independent noise carrier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that E is sufficient for speech perception (Shannon et al 1995;Apoux et al 2013), while FS is important for pitch perception (Smith et al 2002) and lexical tone perception (Xu and Pfingst 2003). Mandarin Chinese is a tone language with four phonologically distinctive tones that are characterized by syllable-level fundamental frequency (F0) contour patterns.…”
Section: Introductionmentioning
confidence: 99%